PERAN KOMUNIKASI PARIWISATA DALAM PENYELENGGARAAN PON XXI ACEH-SUMUT DALAM MENINGKATKAN HUNIAN HOTEL DI MEDAN - Sihombing, Sihombing; Panjaitan, Hadi (Jurnal Ilmiah Akomodasi Agung, 2024)
The organization of the National Sports Week (PON) in Aceh and North Sumatra in 2024 is expected to have a significant impact on the tourism sector, particularly in increasing hotel occupancy in Medan. This article explores the role of tourism communication, supporting factors, and the effects of this major event on the tourism industry. Using qualitative research methods and secondary data analysis, it is found that effective tourism communication, including promotions through social media and collaboration influencers, can attract visitors' attention. Collaboration among the government, hospitality industry players, and travel agents is also crucial for disseminating accurate information regarding available facilities and tour packages. The findings indicate that PON XXI has the potential to increase both visitor numbers and hotel occupancy during and after the event. Furthermore, hotel managers in Medan are advised to develop sustainable communication strategies to promote the city as an attractive tourist destination, thereby providing long-term positive impacts on regional tourism. With a well-planned approach, Medan can maximize its tourism potential and leverage the momentum of PON XXI to attract more tourists in the future.